IoT Bugs and Development Challenges - Makhshari, Amir; Mesbah, Ali (Proceedings / International Conference on Software Engineering, 2021)
IoT systems are rapidly adopted in various domains, from embedded systems to smart homes. Despite their growing adoption and popularity, there has been no thorough study to understand IoT development challenges from the practitioners' point of view. We provide the first systematic study of bugs and challenges that IoT developers face in practice, through a large-scale empirical investigation. We collected 5,565 bug reports from 91 representative IoT project repositories and categorized a random sample of 323 based on the observed failures, root causes, and the locations of the faulty components. In addition, we conducted nine interviews with IoT experts to uncover more details about IoT bugs and to gain insight into IoT developers' challenges. Lastly, we surveyed 194 IoT developers to validate our findings and gain further insights. We propose the first bug taxonomy for IoT systems based on our results. We highlight frequent bug categories and their root causes, correlations between them, and common pitfalls and challenges that IoT developers face. We recommend future directions for IoT areas that require research and development attention.